Software “ROSETTA STONE” en el desarrollo de habilidad del Listening and Speaking del Idioma Ingles en niños de 12 a 15 años de la parroquia San Vicente del cantón San Miguel provincia Bolívar, periodo 2016 - Guaray Guaman, Adan Marcelo (2016)
The project present is results about methodology denominate “ Listening and Speaking Teaching Assisted by Computer ” (LSTAC) in ability development listening and speaking of English between children 12 and 15 years old in from San Vicente Parish, San Miguel Canton, Bolivar Province 2016 period.” The methodology allowed for good results (82%) in a sample of 17 students reaching to an "A1" level according to the Common European Framework of Reference for Languages, improving the level of Listening and Speaking. In addition it allowed to learn Vocabulary, Grammar and basic concepts to formulate dialogues, of personal information that enriches the foreign language fulfilling thus with the objectives raised in this Methodological proposal (ELSAO